The Relationship Between Stress Level and Menstrual Cycle in Final Year Students - Sukmawati, Ima; Ayu Safitri, Nita; Gunawan, Asep; Nur Fauziah, Diny; Solihah, Rosidah (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: According to the World Health Organisation (WHO), 38.45% of adolescent problems are related to menstrual disorders. Menstrual disorders are abnormalities that occur in the menstrual cycle. Signs and symptoms of menstrual disorders include too little or too much menstrual blood, menstrual pain, and depression before menstruation or premenstrual dysphoric disorder. One factor that affects the menstrual cycle is stress. Stress impacts overall physical and psychological health such as insomnia, headaches, personality disorders, anxiety disorders, depression. Final year students as academic individuals are also inseparable from stress in their daily activities which can cause menstrual cycle disorders. Objective: To determine the relationship between stress level and menstrual cycle in final year students at STIKes Muhamamdiyah Ciamis. Method: The research method is quantitative with cross sectional research design. The sampling technique was proportional random sampling using the Slovin formula so that a sample of 63 respondents was obtained, namely final year students at STIKes Muhammadiyah Ciamis. The research instrument was a questionnaire sheet. Data analysis using univariate and bivariate analysis with chi square statistical test. Result: The highest frequency stress level was severe stress category as many as 23 respondents (36,5%). The highest frequency menstrual cycle is normal category as many as 34 people (54.0%). Statistical test results with chi square test obtained (p = 0.036 < 0.05). Conclusion: There is a relationship between stress level and menstrual cycle in final year students at STIKes Muhammadiyah Ciamis.